Modelling the cake filtration on a rotary Nutsche in oscillatory mode - Machač, Ivan; Šiška, Bedřich; Machačová, Ludmila; Doleček, Petr (Univerzita Pardubice, 2004)
As an alternative to a classical Nutsche with a flat filtration surface, a rotary Nutsche has been developed. It is constructed like a circular drum with the bottom half being used as the filter area. The drum is placed on wheels and simple rope drive enables the drum to oscillate. During a batch filtration period, the filter area of RN filter decreases and equations of filtration taking into account the variability of filter face area should be used for the prediction of rotary Nutsche filtering performance. Such equations for filtration in the static (non-oscillatory) mode have been presented earlier. Herein, the model modified for filtration in an oscillatory mode is presented and the results of its numerical solution for filtration of diatomite and cellulose suspensions are compared with those obtained in testing the filtering ability of a pilot plant cylindrical rotary Nutsche.